2017
DOI: 10.20473/jbk.v5i2.2016.135-145
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesiapan Siswi Sekolah Dasar dalam Menghadapi Menarche

Abstract: Puberty among female adolescent occurred when coming to menarche period. The age of menarche among girls in Indonesia has decreased in recent years. It impacts on readiness of menarche among pre puberty female adolescent, both physically and mentally. There were many girls who stated that they didn’t ready to face menarche. The unreadiness of female adolescent on experience menarche will impact to their behavior of vulva hygiene and increase the risk of being infected by sexually transmitted diseases. Surabaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 2 publications
0
7
0
15
Order By: Relevance
“…The following research conducted by Putri (2017) showed that the majority of research subjects in SDN 3 Bantul, Yogyakarta there were 30 respondents from 40 students (71.4%) had sufficient knowledge. In contrast to the research conducted by Lutfiya (2017), young women (61.8%) in Surabaya have lack of knowledge.…”
Section: Discussionmentioning
confidence: 63%
“…The following research conducted by Putri (2017) showed that the majority of research subjects in SDN 3 Bantul, Yogyakarta there were 30 respondents from 40 students (71.4%) had sufficient knowledge. In contrast to the research conducted by Lutfiya (2017), young women (61.8%) in Surabaya have lack of knowledge.…”
Section: Discussionmentioning
confidence: 63%
“…Kurangnya pengetahuan remaja putri juga dapat berdampak pada kesehatan organ reproduksi. Remaja putri kurang memahami bagaimana caranya membersihkan organ reproduksi, cara mengganti pembalut saat menstruasi (Lutfiya, 2017). Berdasarkan penelitian, satu dari tujuh siswi tidak masuk sekolah satu hari ataupun lebih ketika sedang menstruasi.…”
Section: Pendahuluanunclassified
“…Menurut Lutfiya (2016) sebanyak 50% remaja putri memiliki pengetahuan yang kurang tentang menstruasi dan mengatakan tidak siap untuk menghadapi menarche. Hal ini sejalan dengan penelitian yang dilakukan oleh Rohmah et al, (2015) menyatakan bahwa remaja yang memiliki skor tinggi pada pengetahuan tentang menstruasi juga memiliki skor tinggi pada kesiapan menghadapi menarche.…”
Section: Pendahuluanunclassified